MAKING ALL THINGS NEW: Inaugurated Eschatology for the Life of the Church - Edy Gurning (STT Amanat Agung, 2019)
Gladd, Benjamin dan Harmon, Matthew. Making All Things New: Inaugurated Eschatology for the Life of the Church (Grand Rapids: Baker, 2016). xv+197 halaman.